Appropriating the Ethos of Confucius for the Rebuilding of the Nigerian Commonwealth - Emmanuel Williams Udoh (Universitas Negeri Makassar, 2021)
The Nigerian commonwealth has been bastardized by our national political and economic managers. This has given rise to the current cry in search of unity, peace and patriotism of Nigerians. It can be said again that things have fallen apart and the centre seems not to hold any longer. The current wave of corruption, bloodshed, ethnic militia and communal and political subdivisions and carpet crossing at our political arena are clear signs of the deteriorating state of our Nigerian commonwealth. Good Nigerians desire to see Nigeria return back to her former glory of oneness, prosperity and pride. That is why this research explored the ethos of Confucius for the rebuilding of the Nigerian commonwealth. This work which is anchored on the sociological theory of “Structural Functionalism” propounded by Emile Durkheim (1850-1917) and adopted the qualitative or exploratory research method in gathering information. It employed the content analysis approach in examining available printed materials on the subject matter. The findings from the research showed that Nigerians have deviated from the ethical values that had initially been the source of strength and toe the path of selfishness, ethnicity and division. This new path became a path to corruption and disintegration. The research recommends an inclusiveness of human responsibility for improving life; adoption of an ideal political system founded on “ideals of personal conduct” rather than on formerly enacted laws; and adoption of a viable religious ethos that will revitalize the ailing economic, social and political status of the Nigerian commonwealth.